2018
DOI: 10.1002/lary.27747
|View full text |Cite
|
Sign up to set email alerts
|

Wideband tympanometry and absorbance measurements in otosclerotic ears

Abstract: Objectives This study aimed to assess absorbance using a thorough analysis of individual points of its plot in ears with intraoperatively confirmed otosclerosis. To the best of our knowledge, until recently no analyses have been performed that concerned the shape of an absorbance plot and a detailed analysis of its individual points. This study is the first to undertake such an issue. Methods A total of 77 otosclerotic ears were included in the study. Pure tone audiometry, low frequency tympanometry, and wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The multidimensional graphs obtained from WAI enable the clinician to better understand the dynamic characteristics of the middle ear by recognizing specific tympanometric patterns associated with middle ear pathologic change. Niemczyk et al 12 investigated WAI patterns in ears with intraoperatively confirmed otosclerosis by analysing resonance frequency, and number of peaks with detailed descriptions in terms of height and width. Although the patterns were statistically significantly different and provided important diagnostic information in terms of otosclerotic status, this approach appears less helpful clinically for the purpose of differential diagnosis as the absorbance patterns overlap with absorbance graphs found in the normal ear condition and other middle ear disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The multidimensional graphs obtained from WAI enable the clinician to better understand the dynamic characteristics of the middle ear by recognizing specific tympanometric patterns associated with middle ear pathologic change. Niemczyk et al 12 investigated WAI patterns in ears with intraoperatively confirmed otosclerosis by analysing resonance frequency, and number of peaks with detailed descriptions in terms of height and width. Although the patterns were statistically significantly different and provided important diagnostic information in terms of otosclerotic status, this approach appears less helpful clinically for the purpose of differential diagnosis as the absorbance patterns overlap with absorbance graphs found in the normal ear condition and other middle ear disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations have confirmed that absorbance in otosclerotic ears is decreased compared to normal-hearing ears, especially in the low-frequency range [ 1 , 14 , 19 , 20 , 21 ]. The decrease is due to increased stiffness of the vibrating system which in turn gives rise to a decrease in low-frequency acoustic susceptance, and consequently an increase in reflection coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…After stapedotomy, the stiffness associated with otosclerosis is reduced, but compliance of the tympano-ossicular system is increased compared with normal ears, making resonant frequency even lower than normal. 15 21 24 25 27…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown reduced absorbance, or increased reflectance, in otosclerotic ears, 14 15 16 17 18 19 particularly in the low frequency band. This reduction in absorbance occurs due to increased stiffness in the system, which leads to a decreased acoustic sensitivity to low frequencies and, consequently, increased reflection.…”
Section: Introductionmentioning
confidence: 99%